4​(xminus​6)plus2equals6xminus8

1 answer

Let's solve the equation step by step:

Given equation: \[ 4(x - 6) + 2 = 6x - 8 \]

Now, distribute the \(4\) on the left side: \[ 4x - 24 + 2 = 6x - 8 \]

Combine the constant terms on the left side: \[ 4x - 22 = 6x - 8 \]

Next, we will move the \(4x\) to the right side: \[ -22 = 6x - 4x - 8 \] \[ -22 = 2x - 8 \]

Now, add \(8\) to both sides: \[ -22 + 8 = 2x \] \[ -14 = 2x \]

Finally, divide both sides by \(2\): \[ x = -7 \]

Thus, the solution to the equation is: \[ x = -7 \]